The effect of vitamin D supplementation on plasma non-oxidised PTH in a randomised clinical trial. Issue 5 (May 2019) - Ursem, Stan; Francic, Vito; Keppel, Martin; Schwetz, Verena; Trummer, Christian; Pandis, Marlene; Aberer, Felix; Grübler, Martin R; Verheyen, Nicolas D; März, Winfried; Tomaschitz, Andreas; Pilz, Stefan; et al.
Abstract : Objective: PTH can be oxidised in vivo, rendering it biologically inactive. Non-oxidised PTH (n-oxPTH) may therefore give a better image of the hormonal status of the patient. While vitamin D supplementation decreases total PTH (tPTH) concentration, the effect on n-oxPTH concentration is unexplored. We investigated the effect of vitamin D on n-oxPTH concentration in comparison to tPTH and compared the correlations between parameters of calcium, bone and lipid metabolism with n-oxPTH and tPTH. Methods: N-oxPTH was measured in 108 vitamin D-insufficient (25(OH)D <75 nmol/L) hypertensive patients, treated with vitamin D (2800 IE daily) or placebo for 8 weeks in the Styrian Vitamin D Hypertension Trial (NCT02136771). We calculated the treatment effect and performed correlation analyses of n-oxPTH and tPTH with parameters of calcium, bone and lipid metabolism and oxidative stress. Results: After treatment, compared to placebo, 25(OH)D concentrations increased, tPTH decreased by 9% ( P < 0.001), n-oxPTH by 7% ( P = 0.025) and the ratio of n-oxPTH/tPTH increased ( P = 0.027). Changes in phosphate and HDL concentration correlated with changes in n-oxPTH, but not tPTH. Conclusions: tPTH and n-oxPTH decrease upon vitamin D supplementation. Our study suggests that vitamin D supplementation reduces the oxidation of PTH, as we observed a small but significant increase in the non-oxidised proportion of PTH upon treatment. In addition, we found that changes in phosphate and HDL concentration showed a relationship with changes in n-oxPTH, but not tPTH. This may be explained by the biological activity of n-oxPTH. Further research should be carried out to establish the clinical relevance of n-oxPTH.